PECULIARITIES OF POLYSEMY AS A CONCEPTUAL PHENOMENON (TAMADDUN NURI JURNALI, 2024)
The article deals with the issues based on analyzing specific characteristics of polysemy as a conceptual phenomenon. During the development of the meaning of a word, various processes that affect its formal and semantic aspects take place. The presence of polysemy in the language allows not only saving words linguistically, but also ensures the stability and systematicity of relations between the lexical units of the language.